Analisis Perilaku dan Kinerja Struktur Baja dengan Sistem Struktur Diagrid dan Inverted V-Braced - I Putu Agus Putra Wirawan (Universitas Pendidikan Nasional, 2021)
The diagrid structure system is a grid structure system that is applied to buildings with a diagonal shape. This structural system aims to increase the strength and stiffness of the building. In addition, the diagrid structural system can provide a more aesthetic appearance. This structural system is very good for application in medium to high rise buildings. In this study, a comparison of the behavior and performance of the Diagrid (DIA) and Brace Frame (BF) structural system using ETABS 2016 software is carried out. The structural behaviors to be reviewed include stress ratio, deformation, drift ratio and structural weight, while the structural performance includes pushover curves. The geometry of the two buildings uses a span length and width of 3@5m and a total height of 30 m. In this study, results obtained from behavioral analysis in the form of stress ratio is less than 1, the deformation of BF was 58% greater compared to the DIA model, drift ratio of DIA was 35% more rigid than BF and the weight ratio of DIA was 24% lighter compared to BF with the weight ratio of 1.33, while for the performance analysis of the DIA model is 14% better than the BF model. It can be concluded that the DIA structural system is better than the BF.